Attitudes Regarding HPV Vaccinations of Children among Mothers with Adolescent Daughters in Korea - Lee, Kyong-No (The Korean Academy of Medical Sciences, 2017)
The aim of this study, carried out before the beginning of human papillomavirus (HPV) vaccinations as a National Immunization Program (NIP) in Korea in 2016, is to assess the ranges of perceptions and personal experience and their influences on attitudes regarding HPV vaccinations of children, among mothers of adolescent (9–14 years of age) daughters in Korea. From November 2015 to February 2016, we distributed a written questionnaire to mothers who had daughters aged 9–14 years. The questionnaire consisted of several questions, related to knowledge of HPV, personal experiences of HPV vaccination, and attitudes toward HPV vaccinations of their adolescent daughters. Of the 260 questionnaires distributed, 140 participants returned answered ones. And although only 51% of participants were aware that cervical cancer is highly related with HPV infection, 70% said they were willing to vaccinate their daughters, showing that awareness does not coincide with intention to vaccinate. Among the participants showing negative attitudes, 50% were concerned about the vaccination side effects. The more the participants’ pre-knowledge about HPV infection, and about the relationship of HPV to cervical cancer, the more positive their attitudes (P = 0.002, P < 0.001). Our study showed that, as the level of education rose, the proportion of mothers with negative attitudes toward vaccinating their adolescent daughters rose as well. Thus, the provision of correct education by health care providers and accurate information through active advertising may play an important role in increasing the vaccination rate among adolescent girls in Korea.